The translation field in Serbia 1960-1990 - Eraković, Borislava (Stridon, 2021)
The paper presents a chronological overview of diverse translation related activity in Serbia be-tween 1960 and 1990 that led to a successful interplay of four types of perspectives on translation enquiry: Policy, Public, Scientific and Critical (Koskinen 2010). It is based on the data available in periodicals, conference proceedings and other publications issued by two major translator associa-tions and book-length publications on translation theory in Serbia during this period. The analysis presents the events, topics, participants and publications on translation as well as the role of state ideology in the promotion of translation activities. Finally, it is argued that the continuous dialogue between practitioners and scholars on numerous pragmatic questions (translator training, develop-ment of terminologies, the status of the profession and others), as well as on theoretical ones (on the nature of translation theory) led to the emergence of theoretical discourse on translation in Serbia.
Keywords: družbenopolitično prevodoslovje; javno prevodoslovje; Policy Translation Studies; prevajalska društva; Public Translation Studies; Serbian discourse on translation; srbski diskurz o prevajanju; teorija prevajanja; translation theory; translator associations